Changes in crime surrounding an urban home renovation and rebuild programme. (April 2022) - Kondo, Michelle; Degli Esposti, Michelle; Jay, Jonathan; Morrison, Christopher N.; Freisthler, Bridget; Jones, Claire; Yang, Jingzhen; Chisolm, Deena; Branas, Charles; Hohl, Bernadette
Neighbourhood environments are a known social determinant of health. Vacant and abandoned buildings and lots and poor or hazardous housing conditions, combined with crime and violence, can affect residents' health and wellbeing. Nationwide Children's Hospital and its partners launched the Healthy Homes initiative in 2008, which sought to improve nearby residents' health and wellbeing by rejuvenating vacant and abandoned properties and increasing homeownership in the South Side neighbourhood of Columbus, Ohio. Between 2008 and mid-2019 the initiative funded 273 repairs or renovations in this neighbourhood. We conducted a ZIP-code-level comparative case study of the Healthy Homes housing interventions using synthetic control methodology to evaluate changes in crime rate in the intervention area compared with those in a synthetic control area. While findings were mixed, we found some evidence of reduced thefts in the Healthy Homes area, relative to its synthetic control. This initiative to repair, rebuild and increase ownership of housing has the potential to reduce crime rates for neighbours of the Nationwide Children's Hospital.